Creation speakers in all sides direction in acoustics - Головкіна, Людмила Вячеславівна (Technology audit and production reserves, 2012)
The article describes the results of creation in all sides direction speakers are examined. Empiric formulas are offered for the calculation of the kontrapertura acoustic system. Experimental descriptions of the kontrapertura system are analyzed in the near area of listening